First by being last : sequential order bias in a natural experiment - Tan, Glenn Jian Wuen (Nanyang Technological University, 2022)
Sequential order bias arises when a subject is advantaged or disadvantaged because of his/her position in the order. This study attempts to addresses potential concerns in previous research, and extends the literature by examining sequential order bias prevalent in a large number of judges in each performance, with the additional element of random order assignment of performers. Using a large dataset of performance evaluations and serial positions in the singing contest “I am Singer”, our findings are empirically scrutinized and indicate a significant negative causal relationship between the subject’s performance rank and his/her order of performance, suggesting that sequential order bias is inherent in singing competition evaluations. We further discuss the alternative explanations of such phenomenon, the potential avenue for future research, and lastly, the policy implications of sequential order bias.